Virtual world and biometrics as strongholds for the development of innovative port interoperable simulators for supporting both training and R&D. (12th April 2010) - Bruzzone, Agostino G.; Fancello, Gianfranco; Fadda, Paolo; Bocca, Enrico; D'Errico, Gianmarco; Massei, Marina
This paper proposes an integrated solution for port M&S involving distributed interoperable simulators of port cranes; the authors propose the architecture, the description of the model, The containerisation of these simulators for guaranteeing maximum mobility as well as their integration with biomedical devices. The proposed system is designed to be used in operation training of Gantry Crane Operators as well as Research and Development (R&D) support in Container Terminal, Port Plants and Facilities.